Anion effect on obtaining nano-sized metal particules by reduction reaction - Sebati İlhan; Melda Bolat; Kadir Erol; Dursun Ali Köse (MANAS: Journal of Engineering)
The word “nano” means; one in a billion of a physical mass. Nanotechnology has been frequently beneficial branch of science in recent years by applying nanoparticules to various fields. Synthesis of particules in nano is size, has increased the covered surface area in unit volume and this made expanding of using nanoparticules in many different areas. Especially the metal nanoparticules have many advantages leading to development of many ways of synthesis. One of these methods of synthesis is “chemical reduction”. This work makes a research on the anion effects on the size mass nanoparticules of metals Cu(II), Ni(II), Co(II), Zn(II) and Mn(II) after reduction to nano size of sodium bor hidrur which belongs to salt of asetat and chlor, nitrate, sulfate. Depending on the radius ratios and solubility values of metal cations and anions, the nanoparticle obtained from Cu(CH3COO)2 salt has the smallest radius. Nanometal particles with the largest radius were obtained by reduction of Cl- ion salts. Size analyze and passing electrone microscope (SEM) analysis made about the characterization of synthesised nano particules.